Desarrollo de un ERP para la empresa Siscom módulo: control de asistencia. - Iza Iza, Jimmy Humberto (2023)
The technological proposal has been developed atSISCOM Company, an internet service provider inSan Buenaventura parish, Latacunga canton. The main objective was to create a web and mobile application focused on attendance control of the personnel workingin the company. Theidentified problem was attendance the manual registration of workers, which was inefficient. Therefore, the creation of an attendance control was proposed geolocation, in order to determinerecord attendance andemployees location for monitoring the area.The application development process included drafting information on methodologies, tools and techniques were. Interviews and surveys conducted to identify needs. For web application, PHP program with HTML and Laravel 7 was used. For mobile version, Ionic and Angular were used. The XP (Extreme Programming) methodology was implemented to facilitate collaborative work between two people, with iterative delivery of user stories. Mobile D methodology was also used for of the mobile versiondevelopment. The system consists three main actors: the administrator, manager and employees, each with different roles in the system. Through this proposal, the problem was solved by implementing an attendance register based on geolocation. This will allow to efficiently cover the control needs of employees in different companyareas.